Introducing Artificial Intelligence Utilization in Learning to High School Teachers - Djajasoepena, Rafie; Syamsuri, Ady; Nurfais, Ahmad; Bahagia, Katherine Luckman; Kusuma, Felicia; Dewa, Gilang Raka Rayuda; Purnomo, Ariana Tulus; Bhakti, Muhammad Agni Catur; Wandy, Wandy; Triawan, Farid; Githa, Arum; Lestari, Tika Endah; Setiawan, Iwan (Journal of Community Services: Sustainability and Empowerment, 2025)
The development of artificial intelligence (AI) has significantly impacted various sectors, including education. However, based on observation, no AI tool-integrated course has been utilized by teachers at SMA 6 Cirebon. Moreover, based on the pretest assignment, the average understanding of teachers in SMAN 6 Cirebon regarding AI technology was only 55.48%, indicating challenges in implementing AI tools due to a lack of knowledge and practical guidance. To address this issue, a community service activity was held to empower teachers with applicable AI knowledge and skills through a seminar titled "How AI Learns Like a Brain: Implementasi AI dalam Pembelajaran". A qualitative approach was employed, beginning with seminar preparation, AI literature review, and interactive team discussions. Pre- and post-tests showed an increase in understanding of AI technology, with the mean score rising from 55.48% to 67.22% and the median score increasing from 60% to 80%. Finally, this community service recommends ongoing training, the development of AI-integrated lesson plans, hands-on workshops, and collaboration with educational authorities to support the further implementation of AI in teaching.